FcγRIV is required for IgG2c mediated enhancement of RBC alloimmunization - Qiu, Annie; Miller, Anabel; Zotti, Flavia Dei; Santhanakrishnan, Manjula; Hendrickson, Jeanne E.; Tredicine, Maria; Stowell, Sean R.; Luckey, Chance John; Zimring, James C.; Hudson, Krystalyn E. (Frontiers in Immunology, 2022)
Passive immunization with anti-D can prevent maternal alloimmunization to RhD thereby preventing hemolytic disease of the fetus and newborn. Unexpectedly, anti-D fails in some cases and some monoclonal anti-D preparations paradoxically enhances alloimmunization. The underlying mechanisms modulating humoral alloimmunization by anti-D are unknown. We previously reported that IgG antibody subclasses differentially regulate alloimmunity in response to red blood cell (RBC) transfusions in a mouse model; in particular, IgG2c significantly enhanced RBC alloantibody responses. Initial mechanistic studies revealed that IgG2c:RBC immune complexes were preferentially consumed by the splenic dendritic cell (DC) subsets that play a role in RBC alloimmunization. The deletion of activating Fc-gamma receptors (FcγRs) (i.e., FcγRI, FcγRIII, and FcγRIV) on DCs abrogated IgG2c-mediated enhanced alloimmunization. Because DCs express high levels of FcγRIV, which has high affinity for the IgG2c subclass, we hypothesized that FcγRIV was required for enhanced alloimmunization. To test this hypothesis, knockout mice and blocking antibodies were used to manipulate FcγR expression. The data presented herein demonstrate that FcγRIV, but not FcγRI or FcγRIII, is required for IgG2c-mediated enhancement of RBC alloantibody production. Additionally, FcγRI is alone sufficient for IgG2c-mediated RBC clearance but not for increased alloimmunization, demonstrating that RBC clearance can occur without inducing alloimmunization. Together, these data, combined with prior observations, support the hypothesis that passive immunization with an RBC-specific IgG2c antibody increases RBC alloantibody production through FcγRIV ligation on splenic conventional DCs (cDCs). This raises the question of whether standardizing antibody subclasses in immunoprophylaxis preparations is desirable and suggests which subclasses may be optimal for generating monoclonal anti-D therapeutics.